2014
DOI: 10.1186/1472-6882-14-344
|View full text |Cite
|
Sign up to set email alerts
|

Guibitang, a traditional herbal medicine, induces apoptotic death in A431 cells by regulating the activities of mitogen-activated protein kinases

Abstract: BackgroundGuibi-tang (GBT), a traditional herbal formula, mainly has been shown to possess immune regulation, antioxidant and protective effect of the gastric mucosa. Constituent herbs of GBT are frequently used to treat various diseases; however, their pharmacological effects, especially on cancer cells, differ from those of GBT. Furthermore, the molecular mechanisms behind effects of GBT remain unclear. In the present study, we explored the mechanism of chemopreventive/chemotherapeutic efficacy of GBT agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It has been shown that the MAPK family, which includes p38 kinases, extracellular signal-regulated kinases (ERK), and JNK, all play important roles in cell death, differentiation, and survival. 19 JNK and p38 are activated in response to several stress signals, including tumor necrosis factor (TNF) and hyperosmotic conditions, and this activation is associated with induction of apoptosis. 20 ERK activation is induced by growth factors and oxidant injury and plays a major role in regulating cell growth and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the MAPK family, which includes p38 kinases, extracellular signal-regulated kinases (ERK), and JNK, all play important roles in cell death, differentiation, and survival. 19 JNK and p38 are activated in response to several stress signals, including tumor necrosis factor (TNF) and hyperosmotic conditions, and this activation is associated with induction of apoptosis. 20 ERK activation is induced by growth factors and oxidant injury and plays a major role in regulating cell growth and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, cancer cells have self-renewal regulation mechanisms similar to stem cells, and show extensive proliferation properties. Therefore, in addition to their use for in vitro studies of cancer and anti-cancer therapies 14 15 , cancer cells are widely used for general in-vitro cell research and as a model for regenerative medicine 16 .…”
mentioning
confidence: 99%
“…Gleditsia sinensis thorn induced p38 MAPK, ERK1/2 and JNK phosphorylation in human colon cancer cells (26). Guibi-tang (GBT) treatment upregulated the expression of p38, ERK and JNK, which were retained during apoptosis in the A431 cells (27). Ponicin inhibited cell growth by arresting G1-cell cycle and inducing apoptosis in HT29 cells.…”
Section: Discussionmentioning
confidence: 99%